2006
DOI: 10.1111/j.1463-1326.2006.00649.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of constant positive airway pressure therapy on lipid storage, muscle metabolism and insulin action in obese patients with severe obstructive sleep apnoea syndrome

Abstract: These data show that regular CPAP therapy reduces visceral adipose tissue and leptin and improves skeletal muscle metabolites. In obese patients with severe OSAS, regular CPAP use does not improve glucose control, suggesting that the influence of obesity on glucose control dominates over any potential effect of OSAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
71
1
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 47 publications
2
71
1
2
Order By: Relevance
“…Two studies showed that CPAP can reduce the amount of visceral fat [7,8]. However, our negative findings are in agreement with two previous studies [4,9].…”
Section: Sleep-related Disorders I Kritikou Et Alcontrasting
confidence: 37%
See 1 more Smart Citation
“…Two studies showed that CPAP can reduce the amount of visceral fat [7,8]. However, our negative findings are in agreement with two previous studies [4,9].…”
Section: Sleep-related Disorders I Kritikou Et Alcontrasting
confidence: 37%
“…This Japanese study included a very small number of nonobese females, which did not allow for an appropriate analysis stratified by sex. Additionally, the very few studies on continuous positive airway pressure (CPAP) effects on body composition are primarily in obese males, and the results are contradictory [4,[7][8][9]]. …”
mentioning
confidence: 99%
“…CPAP therapy has also been associated with reductions in visceral fat and total cholesterol and increased HDL. 106 As for OSA patients with concomitant type 2 diabetes, CPAP therapy has been linked to better glycemic control and improved insulin sensitivity, although these results have not been consistent. 107 -109 Finally, CPAP has been associated with attenuation in infl ammatory biomarkers and perhaps even improved endothelial function.…”
Section: Cpap Treatment Of Osamentioning
confidence: 81%
“…Similarly, the Swedish Obesity Study reported a three-fold incidence of diabetes and hypertriglyceridaemia in patients with witnessed apnoeas compared to subjects with no OSA at 2 yrs follow-up [110]. Two studies reported that visceral fat decreased after CPAP treatment [103,111] while a more recent study [93] found no change in IR or visceral fat after CPAP for 3 months. Therefore, large longitudinal studies [102].…”
Section: Effects Of Osa Treatmentmentioning
confidence: 97%